Implementation of Sharia-based Financial Literacy in elementary school students - Yus Hermansyah; Mohamad Yudiyanto; Dudi Badruzaman; Anisa Nurlaila (International Journal of Education and Digital Learning (IJEDL), 2023)
This research is motivated by the fact that sharia financial knowledge is needed as part of financial literacy. The public, in this case elementary school students, needs to understand the role and function of sharia financial institutions or organizations, the role of services or products, as well as financial services with sharia or Islamic concepts, including the features of their interests and obligations. The existence of a sharia financial culture can change people's attitudes and perspectives in developing their finances. This research aims to analyze the implementation of financial literacy in sharia-based elementary school students. The research approach used is qualitative with descriptive methods. The results of this research show that the implementation of financial literacy in elementary schools has not been carried out systematically and is still implicit in the context of intra curricular and extracurricular learning. Financial literacy is explicitly taught in Natural and Social Sciences subjects in the independent curriculum, although in practice it has not been proven to increase students' literacy skills. Therefore, it is hoped that the results of this research will be able to encourage teachers to develop financial literacy learning that prioritizes the thinking skills and social skills of elementary school students.